PENGARUH INTELEGENSI DAN MOTIVASI BERPRESTASI TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SEKOLAH MENENGAH ATAS NEGERI DI KECAMATAN TELUKDALAM - Martinus Telaumbanua (Institut Pendidikan Tapanuli Selatan, 2020)
The purpose of this study was to determine how much influence intelligence and achievement motivation have on student learning outcomes in economic subjects at SMA Negeri Telukdalam District.The research method used in this research is a survey method with correlational analysis. Meanwhile, data and information in the field were collected using a questionnaire. Based on the data analysis, the research results show that: 1) There is a significant influence between intelligence and student learning outcomes in economic subjects with a correlation coefficient of 0.342. while tcount is 5.777. The regression relationship is linear with the equation model Ŷ = 58.466 + 0.272 X1 which is significant at the 0.05 level. 2) There is a significant positive effect of achievement motivation on learning outcomes of economic subjects with a correlation coefficient of 0.268 and a coefficient of determination of 7.2. The regression relationship is linear with the equation model Ŷ = 61.772 + 0.196X2. 3) There is a joint positive influence between the independent variable intelligence (X1) and achievement motivation (X2) with the dependent variable teacher work performance (Y) with a coefficient of determination of 16.1. The multiple regression relationship is linear with the equation model Ŷ = 39.574 + 0.6245X1 + 0.161X2. 4) Intelligence (X1) and Achievement Motivation (X2) either individually or collectively make a significant contribution to the Student Learning Outcomes variable (Y). The contribution of each independent variable to the dependent variable is: a) The intelligence variable is 11.7%, b) The motivation variable is 7.2%. The contribution of the two independent variables together to the dependent variable is 16.1%, meaning 83.9% of student learning outcomes are caused by other factors.